Straggler handling approaches in mapreduce framework: a comparative study - Katrawi, Anwar H.; Abdullah, Rosni; Anbar, Mohammed; AlShourbaji, Ibrahim; Abasi, Ammar Kamal (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The proliferation of information technology produces a huge amount of data called big data that cannot be processed by traditional database systems. These Various types of data come from different sources. However, stragglers are a major bottleneck in big data processing, and hence the early detection and accurate identification of stragglers can have important impacts on the performance of big data processing. This work aims to assess five stragglers identification methods: Hadoop native scheduler, LATE Scheduler, Mantri, MonTool, and Dolly. The performance of these techniques was evaluated based on three benchmarked methods: Sort, Grep and WordCount. The results show that the LATE Scheduler performs the best and it would be efficient to obtain better results for stragglers identification.